1999
DOI: 10.1128/jvi.73.8.6307-6318.1999
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Rous Sarcoma Virus RNA Secondary Structure near the Primer Binding Site upon tRNA Trp Primer Annealing

Abstract: Predicted secondary-structure elements encompassing the primer binding site in the 5′ untranslated region of Rous sarcoma virus (RSV) RNA play an integral role in multiple viral replications steps including reverse transcription, DNA integration, and RNA packaging (A. Aiyar, D. Cobrinik, Z. Ge, H. J. Kung, and J. Leis, J. Virol. 66:2464–2472, 1992; D. Cobrinik, A. Aiyar, Z. Ge, M. Katzman, H. Huang, and J. Leis, J. Virol. 65:3864–3872, 1991; J. T. Miller, Z. Ge, S. Morris, K. Das, and J. Leis, J. Virol. 71:764… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…The previously computationally predicted structures of MΨ and PBS [6][7][8]55] are highly consistent with our experimentally determined secondary structure model of the RSV 5 -leader RNA. The structural features of stem loops SL-A, SL-B, SL-C and L3 are identical, although the nucleotides at the 3 -end of the previously predicted MΨ structure are part of a larger stem loop in our structure (Figure 1).…”
Section: Shape Probing and Secondary Structure Analysis Of Rsv 5 -Leadersupporting
confidence: 84%
See 2 more Smart Citations
“…The previously computationally predicted structures of MΨ and PBS [6][7][8]55] are highly consistent with our experimentally determined secondary structure model of the RSV 5 -leader RNA. The structural features of stem loops SL-A, SL-B, SL-C and L3 are identical, although the nucleotides at the 3 -end of the previously predicted MΨ structure are part of a larger stem loop in our structure (Figure 1).…”
Section: Shape Probing and Secondary Structure Analysis Of Rsv 5 -Leadersupporting
confidence: 84%
“…It is likely that tRNA primer annealing stabilizes the overall conformation of the PBS. Indeed, previous studies showed that the PBS undergoes significant structural changes and forms extensive intermolecular interactions upon primer annealing [55]. The tRNA Trp primer is found annealed to the PBS in protease-defective virions, indicating that the Gag precursor is capable of chaperoning the annealing [21].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…surrounding region forms a complex RNA secondary structure, which is important for viral replication (18)(19)(20)(21). The 5 leader sequence, which extends from the PBS to the AUG codon of gag, is complex, with specific sequences that have features of the secondary structure (22)(23)(24).…”
mentioning
confidence: 99%
“…Ty1 and Ty3 exhibit a variation of this theme inasmuch as nucleotides defining the PBS are non-contiguous (8)(9)(10). However, despite these differences, a wealth of genetic and biochemical data indicates that long-range interactions between the tRNA primer and viral RNA genome contribute to the efficiency with which minus-strand DNA synthesis is initiated (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Alternate regions of complementarity between the tRNA primer and viral RNA genome include (i) nucleotides at the tRNA 5 0 terminus in feline immunodeficiency virus (20), (ii) TCC loop nucleotides in Rous sarcoma virus (12), (iii) D-loop nucleotides in Ty1 (14) and Ty3 (6), and (iv) TCC and anticodon loop nucleotides in HIV-1 and HIV-2 (11,13,15,16,18,19,(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%